Understanding collaboration of university, government, and industry leaders to enhance local economic development: a phenomenological study - Douglas, Brianna B., author; Anderson, Sharon K., advisor; Gloeckner, Gene, committee member; Kuk, Linda, committee member; Troxell, Wade, committee member (Colorado State University. Libraries, 2023)
This qualitative dissertation explored the research question, "How do presidents at small private universities collaborate with local government and industry leaders in their host communities to enhance economic development?" The data were collected from three presidents that had been a university president at a qualifying institution for at least three years and had experienced efforts to collaborate with local government and industry to enhance economic development. Data were analyzed using Interpretative Phenomenological Data Analysis and revealed that presidents at small private universities collaborate with local government and industry leaders in four ways: (a) informally, (b) selectively, (c) without the experts, and (d) with mediocre leadership engagement. These findings aligned with three categories of the Wilder framework: environment, membership characteristics, and resources. Three key insights for presidents of small private universities come to light that provide insight into how to successfully collaborate with local government and industry leaders to enhance economic development in their host communities: (a) succeed at being an exceptional leader, (b) foster a culture of adaptability to change, (c) be courageous and establish a history of tripartite collaboration with local government and industry leaders.
Keywords: economic development; leadership; higher education; collaboration